Community empowerment in sport tourism villages through action research - Sufyar Mudjianto; Helmy Firmansyah; Jajat Darajat Kusumah Negara; Arif Wahyudi; Aceng Hilman; Salsa Eka Putri (Universitas Pendidikan Indonesia, 2026)
This community service program was conducted in the Talaga Warna area, focusing on strengthening community capacity in developing a sport tourism-based rural destination. The program was initiated due to the underutilization of natural sport tourism potential and limited community understanding of sport tourism concepts, product diversification, and the use of supporting technologies. The activity aimed to enhance community knowledge, encourage active participation, and identify innovation and technological needs in rural tourism management. The study employed an action research approach with participatory methods, including problem identification, intervention planning, training implementation, and collective reflection. The results indicate an improvement in participants’ understanding of sport tourism-based rural tourism, identification of the potential of nature-based sport tourism, and increased awareness of the importance of technological integration, such as Geographic Information Systems (GIS) and digital platforms. Furthermore, the program produced tangible outputs in the form of innovative nature-based sport tourism packages. These findings highlight that community empowerment through capacity building and participatory approaches plays a crucial role in supporting sustainable rural tourism development. Abstrak Kegiatan pengabdian kepada masyarakat ini dilaksanakan di kawasan Talaga Warna dengan fokus pada penguatan kapasitas masyarakat dalam pengembangan desa wisata berbasis sport tourism. Program ini dilatarbelakangi oleh belum optimalnya pemanfaatan potensi wisata olahraga alam serta keterbatasan pemahaman masyarakat terkait konsep sport tourism, diversifikasi produk wisata, dan pemanfaatan teknologi pendukung destinasi. Pengabdian ini bertujuan untuk meningkatkan pemahaman masyarakat, mendorong partisipasi aktif, serta mengidentifikasi kebutuhan inovasi produk dan teknologi dalam pengelolaan desa wisata. Metode yang digunakan adalah action research dengan pendekatan partisipatif melalui tahapan identifikasi permasalahan, perencanaan intervensi, pelaksanaan pelatihan, serta refleksi bersama masyarakat. Hasil kegiatan menunjukkan adanya peningkatan pemahaman peserta mengenai konsep desa wisata berbasis aktivitas olahraga, identifikasi potensi wisata olahraga alam, serta kesadaran terhadap pentingnya integrasi teknologi seperti Sistem Informasi Geografis (SIG) dan platform digital. Selain itu, kegiatan ini menghasilkan luaran berupa inovasi produk wisata dalam bentuk paket wisata olahraga alam. Temuan ini menegaskan bahwa pemberdayaan masyarakat melalui peningkatan kapasitas dan pendekatan partisipatif berperan penting dalam mendukung pengembangan desa wisata berkelanjutan. Kata Kunci: desa wisata; pemberdayaan masyarakat; sport tourism; teknologi pariwisata